Mangosteen Export Business Strategy at CV A&H Fruits Group - Shabrina Ghaissan; Netti Tinaprilla; Ratna Winandi (School of Business, IPB University (SB-IPB), 2024)
CV A&H Fruits Group was an exporter from Puspahiang, Tasikmalaya Regency, which offered high-quality mangosteen fruit to the Chinese market. In carrying out its business activities, the company faced instability in mangosteen supply and logistics costs, which had increased significantly due to the Covid-19 pandemic. Apart from that, amidst the many uncertain factors in the agricultural industry, companies needed strategies to remain viable and competitive. Therefore, this study examined the business strategy of CV A&H Fruits Group by reformulating its business model. This study used primary data analysis through in-depth interviews and secondary data analysis through literature studies. The purposive method was used to determine respondents consisting of company directors, farmers, competitors, and the Tasikmalaya District Food Crops Service. The data analysis tools used were the Business Model Canvas and SWOT. Based on the SWOT analysis results, five alternative strategies were formulated, namely offering seedless mangosteen, establishing cooperation with logistics services, expanding cooperation with suppliers, improving service management, and improving warehouse management and product quality. These five strategies were applied to the current BMC resulting in a reformulation of the business model that was reflected in the future BMC CV A&H Fruits Group. This reformulation focused on improving value proposition elements by offering seedless mangosteen, enhancing service to prospects and customers, and carrying out cost efficiencies. Company management needed to intensify relationships, collaboration, and/or cooperation with farmers, universities, or the government to maintain sustainable mangosteen supplies; and logistics services to cut logistics costs. Keywords: business model canvas, business strategy, seedless mangosteen, mangosteen, SWOT